Kultus Kesalehan di Tengah Peredaran Gelap: Ambiguitas Komunikasi Agama dan Politik dalam Menangani Krisis Narkoba - Subiantoro, Dedi; Nasution, Hasyimsyah; Azhar, Anang Anas (Islam & Contemporary Issues, 2025)
This study explores the ambiguity of religious and political communication in Indonesia, particularly in the context of increasing drug trafficking, with a focus on Deli Serdang. Employing a qualitative case study approach, the research involved in-depth interviews with religious leaders, community members, and local officials, combined with field observations and document analysis. These methods were conducted in urban and semi-urban areas affected by drug-related issues. The study reveals how Islamic values—such as honesty and compassion—are often manipulated by public figures, including certain religious leaders, to mask or legitimize criminal activity. This instrumentalization of religious symbolism highlights a disconnect between piety and ethical behavior, contributing to a broader moral crisis. Public trust erodes when religious rhetoric is not matched by integrity, weakening community resilience and the effectiveness of anti-drug initiatives. To address this, the paper proposes a transformative Islamic communication model that emphasizes ethical consistency, contextual relevance, and participatory engagement. It also calls for a redefinition of the role of religious leaders—not merely as moral spokespersons but as active agents of social reform. This study contributes to global discussions on religion and public ethics, drawing parallels with cases of symbolic manipulation in other Muslim-majority societies.